TEXT CENTERED EDUCATIONAL DISCOURSE IN THE MIRROR OF CONTEMPORARY VISUAL CULTURE - Alexander A. Polonnikov; Olga N. Kalachikova; Dmitry Yu. Korol; Natalia D. Korchalova (Moscow Polytechnic University, 2016)
The ideological base of the presented research in favor of the provisions of semiotic mediation of human relations with the world and the key role of education as a breeding institution and transmission of semiotic mediators. The main problem discussed here is to try to determine whether there is concordance between the increasing cultural imaging process due to advances in technology, based mainly on the shape code, and in the formation of dominant forms of interaction. In an experimental situation a semiotic conflict between textual and visual mediators created in educational context leads us to the particular tendency. The tendency shows that 'words eat image' and is reflected in cognitive and behavioral phenomena. Working out a pedagogical concept which would establish parity between mediators and contribute to widening discourse repertoire in education is considered to be the main aim of the research presented in the article.